Clinical outcome of rapid diagnosis and antibiotic stewardship in patients with bloodstream infection in Lampang Hospital - Parichart Sakulkonkij; Jackrapong Bruminhent (Cambridge University Press, 2022)
Bloodstream infection is a significant cause of morbidity and mortality. Early diagnosis and appropriate antibiotic treatment contribute to a favorable prognosis. We demonstrate a reduction of time to proper antibiotics and reduced mortality utilizing prompt diagnosis and antibiotic stewardship by infectious diseases physicians at a general hospital in Thailand.